Ischemic Stroke Severity, Stroke Types and Early Mortality in Patients with End-stage Renal Disease - USLU, FERDA; Ozkan, Sibel; USLU, Ferda; Yoldas, Tahir Kurtulus (My University, 2022)
Objective: To compare the demographic characteristics, vascular risk factors, stroke subtypes and early prognosis of patients with end-stage renal disease (ESRD)/normal renal function (NRF) with acute ischemic stroke (IS). Methods: Demographic data and vascular risk factors of patients with acute stroke between August 1 2013-April 1 2015 were determined. Patients diagnosed with ESRD who were receiving dialysis treatment with a glomerular filtration rate below 15, were included in the study. Stroke severity was determined by using the National Stroke Health Stroke scale. To determine the types of IS, “Trial of Org 10172 in Acute Stroke Treatment” TOAST criteria were used. Deaths during hospitalization were used to determine early mortality. Results: Of the 132 patients included in the study, 33.3% had ESRD and 66.6% had normal renal functions (NRF). Demographic characteristics and risk factors did not differ between ESRD and NRF groups. When stroke types were compared, it was determined that stroke with undetermined etiology with more than one etiology was higher in ESRD patients. Of all patients 10.6% died in hospital and this rate was 20.5% in ESRD patients. In the regression analysis, the presence of ESRD increased hospital mortality significantly (risk ratio: 11.6, 95% confidence interval 1.7-77, p=0.011). Conclusion: Our results showed that more than one etiology was seen in acute IS patients with ESRD and ESRD significantly increased the risk of hospital mortality.
Keywords: Stroke; end-stage renal disease; risk factors; stroke subtypes; early prognosis